Le fratture diafisarie di omero in età pediatrica - Casaburi, A.; Lamberti, D.; Busiello, T.; Sorrentino, B.; Siesto, V.; Guida, P. (Lo Scalpello - Journal, 2018)
HUMERAL SHAFT FRACTURES IN THE PAEDIATRIC AGE Humeral shaft fractures are uncommon in children. They occur with bimodal distribution, presenting peaks in the first and third childhood. The treatment differs according to age and fracture complexity. Most of them generally occur at the medial third of humeral bone, below the distal insertion of the deltoid. The management of minimally dislocated fractures is non-surgical, thanks to children bone remodelling capacity. Surgery is indicated in open fractures, multiple trauma, compartment syndromes and inadequate closed reduction. The elastic intramedullary nailing is the most used therapeutic approach. It is a minimally invasive, simple technique with a very low complication rate.